Neonatal invasive disease caused by Streptococcus agalactiae in Europe: the DEVANI multi-center study - Lohrmann, Florens; Hufnagel, Markus; Kunze, Mirjam; Afshar, Baharak; Creti, Roberta; Detcheva, Antoaneta; Kozakova, Jana; Rodriguez-Granger, Javier; Sørensen, Uffe B Skov; Margarit, Immaculada; Maione, Domenico; Rinaudo, Daniela; et al. (Infection, 2023)
PURPOSE: Group B streptococcus (GBS) remains a leading cause of invasive disease, mainly sepsis and meningitis, in infants < 3 months of age and of mortality among neonates. This study, a major component of the European DEVANI project (Design of a Vaccine Against Neonatal Infections) describes clinical and important microbiological characteristics of neonatal GBS diseases. It quantifies the rate of antenatal screening and intrapartum antibiotic prophylaxis among cases and identifies risk factors associated with an adverse outcome. METHODS: Clinical and microbiological data from 153 invasive neonatal cases (82 early-onset [EOD], 71 late-onset disease [LOD] cases) were collected in eight European countries from mid-2008 to end-2010. RESULTS: Respiratory distress was the most frequent clinical sign at onset of EOD, while meningitis is found in > 30% of LOD. The study revealed that 59% of mothers of EOD cases had not received antenatal screening, whilst GBS was detected in 48.5% of screened cases. Meningitis was associated with an adverse outcome in LOD cases, while prematurity and the presence of cardiocirculatory symptoms were associated with an adverse outcome in EOD cases. Capsular-polysaccharide type III was the most frequent in both EOD and LOD cases with regional differences in the clonal complex distribution. CONCLUSIONS: Standardizing recommendations related to neonatal GBS disease and increasing compliance might improve clinical care and the prevention of GBS EOD. But even full adherence to antenatal screening would miss a relevant number of EOD cases, thus, the most promising prophylactic approach against GBS EOD and LOD would be a vaccine for maternal immunization.
Keywords: Female; novorozenec; Infant; kojenec; Humans; Europe; těhotenství; Antibiotic Prophylaxis; Evropa; lidé; Streptococcal Infections; infekční komplikace v těhotenství; ženské pohlaví; Pregnancy; streptokokové infekce; Pregnancy Complications, Infectious; Infant, Newborn; Streptococcus agalactiae; antibiotická profylaxe